DISTRIBUTION AND BIOACCUMULATION OF HEAVY METALS Pb AND Cd ON BIVALVES Anadara nodifera, Meretrix lyrata, AND Solen lamarckii IN COASTAL WATERS OF THE WEST MADURA STRAIT - . Ahyar; Dietriech G. Bengen; Yusli Wardiatno (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Madura strait receives waste disposal from various activites in the mainland, making it vulnerable to contamination of harmful pollutants. Some of the harmful pollutants are heavy metal Pb and Cd. The high concentration Cd and Pb give negative impacts to the biota including bivalves. This study was conducted to assess the distribution of heavy metals Pb and Cd in the waters and their accumulation in bivalves Anadara nodifera, Meretrix lyrata, and Solen lamarckii in coastal waters of the West Madura Strait. Heavy metal analysis refer to APHA 2012 using AAS. The results showed that concentration of Cd and Pb in water were below the quality standards, while in sediment were above the standard (Cd of 7.20 mg/kg and Pb of 62.06 mg/kg). The concentration of Cd in bivalve were different among the species tested A. nodifera of 6.10 mg/kg, M. lyrata of 3.65 mg/kg, and S. lamarckii of 2.74 mg/kg, as well as Pb concentration A. nodifera of 60.10 mg/kg, M. lyrata of 51.48 mg/kg, and S. lamarckii of 45.29 mg/kg). These results indicated that the three shells have exceeded the maximum limit of heavy metal contamination in food (Cd of 1.0 mg/kg and Pb of 1.5 mg/kg). Keywords: bivalve, heavy metal, Madura Strait